The European Political Community: What’s Up? - Matthijs, Herman (Advances in Social Sciences Research Journal, 2022)
Since the beginning of October 2022 the European continent has a new institution: “The European Political Community” (EPC). It’s a meeting of 44 European countries and the leading institutions of the European Union (EU). This article overviews the history and the realisation of the EPC Also the memberships and the aims are a part of this study concerning the most recent European institution.